HUMAN CAPITAL DEVELOPMENT AND ECONOMIC GROWTH NEXUS IN NIGERIA (Journal of the Management Sciences, 2024)
This study examines human capital development and economic growth nexus in Nigerian using a secondary time series data. The study applied an econometric regression technique of the Ordinary Least Square (OLS) to ascertain the effect of macroeconomic growth induced variables on human capital development in Nigeria. Our findings from the cointegrating regression result test suggest that there is a strong evidence of cointegration between dependent variable (HCD) and the independent Variables. Also the study revealed a long-run causal relationship between dependent variable (HCD) and the independent Variables. It could be observed from our findings that the relationship between some of the variables like TGE, TEE, THE, and FDI and human capital development is positive while that of LEI is negative. This means that TGE, TEE, THE, and FDI have direct relationships with human capital development. In other words, an increase in TGE, TEE, THE, and FDI will results to a rise in human capital development whereas an increase in LEI will probably result in a fall in human capital development. In addition, the results show that TGE, TEE, THE, and FDI have statistical significance on human capital development in Nigeria while LEI is statistically insignificance on human capital development. This study therefore recommends that the government should give educational grants, provide vocational training, provide basic health facilities; enhance the competitiveness of the economy. This will avail the country the enhanced entrepreneurial creativity, a suitable, competent, healthy and educated labor force to contribute meaningfully to national development. The government should make adequate budget for education in line with the UNESCO recommendation. This will help facilitate proper administration of financial revenues and other school resources. There is the need for increased government funding for health care. The will help reduce the challenges in healthcare and the increasing medical tourism outside the country and consequently enhance the countries life expectancy. The government should create a secured and business friendly environment to help attract FDI in the country.
Keywords: Total Government Expenditure, Recurrent and Capital Expenditure, Education Expenditure, Health Expenditure, Life Expectancy Index, Foreign Direct Investment